Mouse embryogenesis requires the tissue factor extracellular domain but not the cytoplasmic domain - Parry, Graham C.N. (American Society for Clinical Investigation, 2000)
Recent studies indicate that tissue factor (TF) acts in embryogenesis, metastasis, and angiogenesis. Three independent groups showed that targeted disruption of the murine TF (mTF) gene results in 90% lethality of mTF null embryos at embryonic days 9.5–10.5. We have demonstrated that expression of wild-type human TF (hTF) from a minigene rescues the embryonic lethality of mTF null embryos. To investigate the role of TF in embryogenesis, we made mutant hTF minigenes whose products either bound FVII/VIIa at a reduced level or lacked the cytoplasmic domain. Two independent transgenic lines expressing the hTF extracellular domain mutant failed to rescue the embryonic lethality of mTF null embryos, suggesting that FVII/VIIa binding by TF, proteolytic activity by the TF/FVIIa complex, or both were required for embryogenesis. In contrast, two transgenic lines expressing the hTF cytoplasmic domain mutant rescued the embryonic lethality of mTF null embryos, indicating that the cytoplasmic domain of TF was not required for embryogenesis. We propose that TF/FVIIa-dependent extracellular protease activity is required for embryogenesis.